THE ESTABLISHMENT OF PERMANENT STRUCTURED COOPERATION TO INCREASE INTEGRATION AND INDEPENDENCE EUROPEAN REGIONAL MILITARY COOPERATION - Hardi Alunaza; Bastian Andhony Toy (Indonesian Association for International Relations, 2021)
This paper aims to discuss the efforts of the European Union in enhancing integration and defense-security cooperation through the establishment of Permanent Structured Cooperation. This paper seeks to answer how the formation of PESCO can increase the integration and independence of military cooperation between EU member states. Whereas before there has been a North Atlantic Treaty Organization as a security pillar that has long been recognized in the European region. The author uses the theory of regional security complex and the concept of collective security in analyzing related phenomena. This research uses descriptive method with qualitative approach. The data collection technique is literature study consisting of books, journals, and including data from reliable websites to support the explanation of this paper. The results of this research indicate the establishment of PESCO as a form of implementation of Article 42 paragraph 6 of the Lisbon Treaty in 2009 concerning the efforts of member countries in establishing defense-security cooperation within the European Union framework. The establishment of the PESCO was also based on doubts by the European Union on the role of the US in NATO, but PESCO did not directly replace NATO but rather as a complement to autonomous and effective crisis resolution.